The Influence of Organizational Culture to Innovation Behavior: A Hierarchical Linear Modelling Approach - Siswanti, Yuni; Nurhariati, Emmy (Journal of International Conference Proceedings, 2022)
Purpose – The purpose of this paper is to use Hierarchical Linear Modelling Approach of the studies that have analyzed the impact of organizational culture (innovative-oriented culture, learning culture, adhocracy culture, clan culture, hierarchical culture, and market/rational culture) on innovative behavior.Design/methodology/approach – The authors carried out a Hierarchical Linear Modelling (HLM). Based on a total of 240 in SMEs actors of culinary creative business Sleman Regency, Yogyakarta, Indonesia.  Data collection with questionnaires and interviews.Findings – After reporting the findings of the HLM, the authors discuss how a variety of culturally related factors combine to facilitate or restrict innovation performance in their corresponding cluster. The findings highlight the complex and idiosyncratic relationship between culture and innovation. Future research lines are recommended.Research limitations – The data in this study is gathered using a cross-sectional method. Future research will be much improved if it is done as a longitudinal study over a period of time, so that the consistency of respondents’ answers on the same variables and instruments can be known.Practical implications – The paper offers interesting implications for managers and academia. For business practitioners, this study can provide a useful reference regarding the role of cultures in the corporate internal management or international operations; especially for small business in culinary, the study can provide a current research landscape and development process in this field.Originality/value – The findings are derived from a hierarchical linear modelling (HLM) that has studied the influence of culture on innovation behavior. Study about the influence of organizational culture on innovation using HLM is very limited, especially in small and medium-sized businesses. In addition, implications and insights as to where future research might be usefully inquired in this field are provided.Keywords: Organizational culture; Innovative Behavior; Hierarchical Linear Modelling